2016 24th Mediterranean Conference on Control and Automation (MED) 2016
DOI: 10.1109/med.2016.7536019
|View full text |Cite
|
Sign up to set email alerts
|

Interval observer design for Linear Parameter-Varying systems subject to component faults

Abstract: Abstract-In this paper an interval observer for Linear Parameter-Varying (LPV) systems is proposed. The considered systems are assumed to be subject to parameter uncertainties and component faults whose effect can be approximated by parameters deviations. Under some conditions, an interval observer with discrete-time Luenberger structure is developed to cope with uncertainties and faults ensuring guaranteed bounds on the estimated states and their stability. The interval observer design is based on assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Indeed, in (36) and thus in (38), the dependence between the variables x k and |x k | is not taken into account. According to (21), the magnitude of the lower and upper bounds of the state estimate can be expressed as a multimodel expression based on…”
Section: Theorem 2 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in (36) and thus in (38), the dependence between the variables x k and |x k | is not taken into account. According to (21), the magnitude of the lower and upper bounds of the state estimate can be expressed as a multimodel expression based on…”
Section: Theorem 2 Systemmentioning
confidence: 99%
“…The second approach 9-13 consists in explicitly building an interval observer from the interval model of the system. Then, solving the interval state equations of the observer, the upper and lower bounds of the state variable estimates are provided.Studies on systems with bounded uncertain parameters can be found in several areas of automatic control such as stability analysis, 14,15 state estimation, 8,16,17 synthesis of iterative learning control law, 18 system diagnosis, 19,20 components fault detection, 21,22 data analysis, 23 model sensitivity analysis, 24 regression with abnormal values, 25 and classification. 26 Roughly speaking, uncertainties in the measures and in the parameters are handled in two main ways.…”
mentioning
confidence: 99%
“…Theorem 1. The switched observer (9) is a switched UIO for system (8) if and only if the following conditions are satisfied:…”
Section: Vehicle Fault Detectionmentioning
confidence: 99%
“…In this paper, zonotopes are used to provide the interval enclosing the unknown true residual vector. The advantage of using zonotopes is that monotonicity property is no longer needed as in [8], [9], [11] allowing to consider the whole set of possible trajectories. The zonotope-based approaches in fault detection has already been investigated in the literature, see for instance [5], [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the interval observers theory, the uncertainties are assumed to be unknown but bounded with a priori known bounds. In the literature, interval observers are applied to several classes of nonlinear systems [27], [23], discrete-time systems [22], [6] and linear systems [10], [17].…”
Section: Introductionmentioning
confidence: 99%